A study on customer perception : Mesra convenience store / Rita Paul - Paul, Rita (2007)
This study was conducted to identify the customer evaluation towards the MESRA convenience store. Customer perceptions consist of customer expectation and customer satisfaction. Customer perception is one of the key for MESRA to identify what basically customers expect from their services in terms of price, quality of goods and service, choices, branded product, promotion of goods, atmosphere and store layout towards the MESRA convenience store whether these customer perception can satisfy their customer expectation and thus find out additional ways that can be used by the MESRA convenience store to attract more customers to come MESRA convenience store. The research design used is descriptive study, and both primary and secondary data regarding the study were gathered. The target population in this study is customers who visit to this four MESRA convenience stores which selected by researcher which consist 160 respondents. The respondents were selected through convenience sampling. In analyzing the data, frequency distribution and cross tabulation were used.